Water adsorption isotherms and thermodynamic properties of germinated pumpkin seeds flours - Maria Suiane de Moraes; Alexandre José de Melo Queiroz; Rossana Maria Feitosa de Figueirêdo; Joana D’arc Paz de Matos; Luís Paulo Firmino Romão da Silva; Francislaine Suelia dos Santos; Semirames do Nascimento Silva; Adolfo Pinheiro de Oliveira (Revista Ciência Agronômica, 2023)
ABSTRACT The use of residues resulting from the processing of agricultural products is an widely studied topic, which is justified by the need to reduce costs and by the search for productive sustainability, which has as one of its principles the full use production, reducing waste and therefore increasing the amount of products extracted per unit of area. Residual seeds, resulting from the production of fruit pulps, are rich in nutrients and with the potential to be further improved by the application of germination, increasing the protein content and the content of bioactive compounds. However, in the germination process, the product acquires a high water content, requiring immediate drying and control of the water adsorption kinetics after dehydration. Therefore, the objective of this study was to determine the water adsorption isotherms of germinated seeds flours from pumpkins of three varieties at temperatures of 15, 25 and 35 °C, to obtain the most appropriate mathematical model to describe the hygroscopic behavior and to determine the thermodynamic properties of water adsorption, through the values of the integral isosteric heat, differential entropy, differential enthalpy and Gibbs free energy for the studied conditions. The GAB and Peleg models fit the experimental data well. With increasing water activity, there was a reduction in isosteric heat and entropy. The enthalpy-entropy compensation theory was confirmed. Gibbs free energy was negative for all temperatures, increasing with increasing equilibrium water content, demonstrating that it is a spontaneous process.